2021
DOI: 10.3920/wmj2020.2662
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary aflatoxin on biochemical parameters and histopathology of liver in Matrinxã (Brycon cephalus) and Pacu (Piaractus mesopotamicus) fish

Abstract: The objective of this study was to evaluate biochemical parameters and histopathology of liver in Matrinxã (Brycon cephalus) and Pacu (Piaractus mesopotamicus) fish chronically exposed to dietary aflatoxins. Fish feed was artificially contaminated with aflatoxins and the treatments were: Control – feed without toxin; Treatment A – feed + 10 μg aflatoxin B1 (AFB1)/kg; Treatment B – feed + 20 μg AFB1/kg; and Treatment C – feed + 50 μg AFB1/kg. Matrinxã and Pacu juvenile fish were placed in tanks for 180 days. Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
1
0
3
Order By: Relevance
“…However, some variations were observed depending on the Chlorella vulgaris concentration. Michelin et al, 2021 showed that Aflatoxin can reduce immune parameters of fish such as Lysozyme, ACH50, Ig, MPO, NBT, C3, and C4 while Fadl et al (2021) reported an increase in the same parameters after adding Dunaliella algae to the dietary. Likewise in this study, Lysozyme activity was increased in the blood of common carp, under the Chlorella vulgaris diet while the highest immune responses were observed in the fish fed by diets containing 5% Chlorella vulgaris except for Ig and Peroxidase which are higher in 10% of Chlorella vulgaris dry powder dietary fed fish.…”
Section: Discussionmentioning
confidence: 99%
“…However, some variations were observed depending on the Chlorella vulgaris concentration. Michelin et al, 2021 showed that Aflatoxin can reduce immune parameters of fish such as Lysozyme, ACH50, Ig, MPO, NBT, C3, and C4 while Fadl et al (2021) reported an increase in the same parameters after adding Dunaliella algae to the dietary. Likewise in this study, Lysozyme activity was increased in the blood of common carp, under the Chlorella vulgaris diet while the highest immune responses were observed in the fish fed by diets containing 5% Chlorella vulgaris except for Ig and Peroxidase which are higher in 10% of Chlorella vulgaris dry powder dietary fed fish.…”
Section: Discussionmentioning
confidence: 99%
“…Para especies tropicales semejantes, se tienen mortalidades en alevinaje hasta 10%, para cultivo de gamitana, paco y policultivo de paco y gamitana en estanques de tierra y geomembrana (Dañino et al, 2009;Suárez et al, 2006;Sandoval, 2006). Por lo que el cultivo se vio ileso de presencia de agentes patógenos que puedan perjudicar a los ejemplares y disminuir la sobrevivencia como es el caso de las aflatoxinas que suelen presentarse y acumularse en los tejidos de los individuos, de tal manera que puedan influenciar los resultados finales en cuanto al peso y longitud, tal como lo demuestra Michelin et al (2021) en su experimentación, dando a conocer los efectos tóxicos debido a la susceptibilidad de B. cephalus y P. mesopotamicus a la exposición a diferentes concentraciones de aflatoxinas B1. Al igual que Rivadeneira et al (2020) donde revela los efectos causados por Spirocamallus y Nematoda en B. cephalus, considerándolos como un gran problema en la salud de los peces.…”
Section: Tasa De Sobrevivenciaunclassified
“…La ALP, es una enzima que se encuentra en el hígado y los huesos y es importante para descomponer las proteínas. Si los niveles de ALP en plasma son más altos de lo normal, es posible que el hígado sufra de alguna enfermedad o daño, como una vía biliar obstruida, o exista alguna enfermedad ósea (Michelin et al 2021b).…”
Section: Susceptibilidad De Las Especies a Aflatoxina Alteraciones He...unclassified
“…Los resultados obtenidos para la acumulación excesiva de grasa en el hígado (esteatosis) se corresponden a lo reportado por Michelin et al (2021b) para la misma especie en los primeros 30 días de exposición. Donde los autores indican que la exposición a las aflatoxinas en la dieta provoca cambios en el hígado, como la muerte celular y la degeneración grasa e hidrópica.…”
Section: Indicadores De Hepatotoxicidadunclassified